Visual rehabilitation in the virtual in pandemic times: experience report - de Oliveira, Charles Henrique Andrade; Marinho, Daniely Mendes; Silva, Yani Sarmento Pacheco (Seven Editora, 2023)
Social isolation (quarantine) was one of the main measures adopted during the pandemic, with the separation and restriction of people’s movement, aiming to reduce the risk of infection, and thus, the spread of the virus and the reduction of new cases, which could lead people to experience in negative ways, such as discomfort, the feeling of loss of freedom, loneliness, boredom, suicide, anxiety attacks, panic, anger, among others (ZWIELEWSK et al., 2020). DOI: https://doi.org/10.56238/devopinterscie-051